2019
DOI: 10.1021/acsami.9b04769
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Microparticles with Defined Surface Chemistry and Topography Mediate the Formation of Stem Cell Aggregates and Cardiomyocyte Function

Abstract: Surface-functionalized microparticles are relevant to fields spanning engineering and biomedicine, with uses ranging from cell culture to advanced cell delivery. Varying topographies of biomaterial surfaces are also being investigated as mediators of cell−material interactions and subsequent cell fate. To investigate competing or synergistic effects of chemistry and topography in three-dimensional cell cultures, methods are required to introduce these onto microparticles without modification of their underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Microparticles loaded with drugs, growth factors or proteins, are able to achieve specific and controlled delivery to cell cultures or as treatments, with the release being tuned further by adjusting the size and internal structure of the particles [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Alternatively, they can be used as a tool to direct stem cell fate, modulate the phenotype of other cells or to provide a realistic 3D environment for culture by forming scaffolds [ 3 , 12 , 13 , 14 ]. Their abilities in this role can be further enhanced by introducing specific chemistries, topographies or porosity [ 12 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microparticles loaded with drugs, growth factors or proteins, are able to achieve specific and controlled delivery to cell cultures or as treatments, with the release being tuned further by adjusting the size and internal structure of the particles [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Alternatively, they can be used as a tool to direct stem cell fate, modulate the phenotype of other cells or to provide a realistic 3D environment for culture by forming scaffolds [ 3 , 12 , 13 , 14 ]. Their abilities in this role can be further enhanced by introducing specific chemistries, topographies or porosity [ 12 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, they can be used as a tool to direct stem cell fate, modulate the phenotype of other cells or to provide a realistic 3D environment for culture by forming scaffolds [ 3 , 12 , 13 , 14 ]. Their abilities in this role can be further enhanced by introducing specific chemistries, topographies or porosity [ 12 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important as topography influences eukaryotic cell and bacterial surface attachment. [ 11–13 ] As a consequence, it is important to move from the design of 2D to 3D structures in order to gain a deeper understanding of the interaction of cells with their immediate extracellular environment and, consequently, derive more realistic biological models/assays that mimic real‐life conditions. [ 14 ] Polymeric microparticles are a simple 3D structure that have numerous healthcare applications including tissue engineering, diagnostics, and drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16,17 ] This presents a problem for biomaterials, as numerous studies have shown that biological‐surface interactions are dependent on surface chemistry. [ 13,16,18,19 ] For example, the presence of residual surfactant, such as the commonly used poly(vinyl alcohol‐co‐vinyl acetate) (PVA), has been shown to mask surface chemistry and impact on the resultant bacterial attachment properties [ 16 ] Thus, new approaches are required to produce particles which exhibit diverse surface chemistries where the process of preparation does not interfere with surface chemistry.…”
Section: Introductionmentioning
confidence: 99%